Evaluating and improving terminal hygiene practices on broiler farms to prevent Campylobacter cross-contamination between flocks. (June 2017) - Battersby, Tara; Walsh, D.; Whyte, P.; Bolton, D.
Abstract: The objectives of this study were to evaluate current cleaning practices in broiler houses by testing a range of sites after cleaning and disinfection and to test the efficacy of the most commonly used methods in a commercial broiler house after flock harvesting. Cleaning procedures on 20 broiler houses (10 separate farms) were examined by testing a range of sampling points (feeders, drinkers, walls, etc.) for total viable count (TVC), total Enterobacteriaceae count (TEC) and Campylobacter spp. after cleaning and disinfection, using culture based methods. In a second experiment, the six most commonly used commercially available disinfectants and/or detergent products were evaluated. The results of the first study demonstrated that critical areas in 12 of the 20 broiler houses were not effectively cleaned and disinfected between flocks as the tarmac apron, ante-room, house door, feeders, drinkers, walls, columns, barriers and/or bird weighs were Campylobacter positive. Thermal fogging with the combination of potassium peroxymonosulfate, sulfamic acid and sodium chloride (5%, v/v) or the glutaraldehyde and quaternary ammonium complex (0.3%, v/v) were the most effective treatments while other disinfectant treatments were considerably less effective. It was therefore concluded that farmers should review their broiler house cleaning and disinfection procedures if Campylobacter cross-contamination between successive flocks is to be prevented. Highlights: Current cleaning practices on broiler farms are ineffective. Several sites, including feeders and drinkers were campylobacter positive after disinfection. The most effective disinfection methods are identified.